2019
DOI: 10.1186/s12884-019-2642-7
|View full text |Cite
|
Sign up to set email alerts
|

TORCH screening used appropriately in China?─three years results from a teaching hospital in northwest China

Abstract: ObjectivesTORCH infections caused by Toxoplasma gondii (TOX), rubella virus (RV), cytomegalovirus (CMV) and herpes simplex virus 1,2 (HSV-1,2) are associated with congenital anomalies. The study aimed to analyze the characteristics of TORCH screening in reproductive age women.MethodsA total of 18,104 women (2015–2017) from a teaching hospital in Xi’an, China, were enrolled in the study. The characteristics of TORCH screening, i.e., the application of TORCH test, the seroprevalence, the impact of age, periods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
(22 reference statements)
1
8
1
Order By: Relevance
“…Upon assessing the total burden of parvovirus B19 among pregnant women, the highest risks of acquiring an infection during pregnancy were estimated for Poland and Finland [39]. In contrast, a recently published study suggested that the seroprevalence of ToRCH pathogens is not affected by age [9]. In the present study, the seroprevalence of antibodies against parvovirus B19 in Poland were among the highest, reflecting low risk of acquiring infection when compared to, e.g.…”
Section: Parvovirus B19contrasting
confidence: 61%
See 2 more Smart Citations
“…Upon assessing the total burden of parvovirus B19 among pregnant women, the highest risks of acquiring an infection during pregnancy were estimated for Poland and Finland [39]. In contrast, a recently published study suggested that the seroprevalence of ToRCH pathogens is not affected by age [9]. In the present study, the seroprevalence of antibodies against parvovirus B19 in Poland were among the highest, reflecting low risk of acquiring infection when compared to, e.g.…”
Section: Parvovirus B19contrasting
confidence: 61%
“…A seroprevalence study from 2010 found that anti-HSV-1 seroprevalence was 72% but varied with age and among Brazilian regions [26]. The observation of age dependency is contrary to a recently published study in a Chinese panel suggesting that the seroprevalence of anti-HSV-1 antibodies is not affected by age [9]. In Brazilian women who participated in the cervical cancer screening program, the prevalence of anti-HSV-1 was 23% [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary infections caused by ToRCH pathogens are the major cause of BOH, and this is well corroborated in published studies both locally [2,19,23] and elsewhere [1,5,22]. This study also observed a higher seroprevalence of ToRCH infections in pregnant women with BOH.…”
Section: Discussionsupporting
confidence: 89%
“…Nowadays, to screen HBV infections in prepregnancy and reproductive-age women, the HBsAg test is recommended [ 8 ]. It is a normal initial detection of the TORCH pathogen which is important for treatment and prevention strategies for adverse fetal outcomes [ 9 ]. The characteristic of these pathogens is that they are asymptomatic at the beginning of the infection, and they cannot be diagnosed based on their clinical features.…”
Section: Introductionmentioning
confidence: 99%